Overprotective, Percaya Diri dan Kemandirian Anak - Sutanto, Lisda (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This research aims to find out the relationships among over protect-tive and self-confidence with autonomy. The study involved 118 sixth grade elementary school children age 12 to 13 years to complete self-report of auto-nomy, overprotective and self-confidence. The results of data measurements were analyzed with multiple regression. The results of analysis showed: 1) there is a significant relationship between overprotective and self-confidence with autonomy, 2) there was no correlation between over protective with auto-nomy, and 3) there is a positive and significant relationship between the self-confidence and autonomy. The research findings are discussed in the context of child development. Keywords: overprotective, self-confidence, autonomy